Exploration of Sound Wave Concept in the Making and Playing of Yogyakarta Gamelan: STEM Learning Approach - Rika Tri Intan Lestari; Sudi Dul Aji; Akhmad Jufriadi (Universitas Lambung Mangkurat, 2025)
This study explores the concept of sound waves in the making and playing of Yogyakarta gamelan through a STEM (science, technology, engineering, and mathematics) learning approach, addressing the urgent need for scientific documentation amid the declining sustainability of this cultural heritage. Using a descriptive qualitative method with a case study design, the research examines the material composition, forging techniques, and acoustic properties of gamelan, incorporating insights from four experienced gamelan craftsmen and a gamelan practitioner (wiyaga) in Yogyakarta. Findings reveal that the optimal bronze composition (a 77:23 copper-tin ratio) and traditional manufacturing processes significantly influence sound characteristics, such as sustain, harmonic richness, and tonal depth, aligning with principles of material physics (Young's modulus, density, and damping coefficient) and vibration mechanics. Despite practitioners' reliance on empirical knowledge, their techniques demonstrate an implicit understanding of STEM concepts, particularly in tuning and sound optimization. However, a disconnect remains between scientific terminology and traditional practice, highlighting the need for culturally sensitive STEM integration in gamelan education. The study concludes that a holistic STEM approach can bridge scientific and cultural perspectives, supporting both the preservation of Yogyakarta gamelan and innovative educational models. Recommendations include STEM-based training for artisans and further research on alternative materials while preserving traditional sound aesthetics.